Prognostic value of thrombocytopenia during hospitalizations in intracerebral hemorrhage patients - Feng, Hao; Luo, Xiaoquan; Fu, Anhui; Wang, Ruoran; Qiao, Fei (Frontiers in Neurology, 2024)
BackgroundThe thrombocytopenia influences prognoses of critically ill patients. There are few studies exploring the prognostic value of thrombocytopenia among ICH patients. We perform this study to explore the correlation between thrombocytopenia at different timepoints of hospitalizations and mortality of ICH.MethodsICH patients recorded in the Medical Information Mart for Intensive Care-III were selected for this observational study. The thrombocytopenia, defined as platelet <150 × 109/L, was divided into three categories: baseline thrombocytopenia (thrombocytopenia occurred at admission), acquired thrombocytopenia (thrombocytopenia developed since the second day after admission), multiple thrombocytopenia (baseline thrombocytopenia + acquired thrombocytopenia). The main outcome in this study was the 30-day mortality of ICH patients. The univariate and multivariate logistic regression was sequentially performed to discover risk factors of mortality and confirm the correlation between thrombocytopenia groups and mortality of ICH.Results66.5% of 902 ICH patients did not experience the thrombocytopenia since admission. 2.2, 14.5 and 16.7% ICH patients showed the baseline thrombocytopenia, acquired thrombocytopenia initial and multiple thrombocytopenia, respectively. The GCS did not show significant difference between thrombocytopenia groups (p = 0.118). The multiple thrombocytopenia group had the highest incidence of mechanical ventilation (p = 0.041), mortality (p < 0.001), and the longest length of ICU stay (p < 0.001), length of hospital stay (p < 0.001). The multivariate logistic regression found age (p < 0.001), GCS (p < 0.001), glucose (p = 0.013), mechanical ventilation (p = 0.002) was correlated with the mortality of ICH patients. Only the multiple thrombocytopenia group showed significant influence on the mortality of ICH (p = 0.002) in the multivariate logistic regression.ConclusionSingle initial thrombocytopenia at admission dose not influence the mortality of ICH patients. ICH patients experiencing both initial thrombocytopenia and acquired thrombocytopenia have significantly higher mortality risk. The blood platelet level of ICH patients should be monitored continuously during hospitalizations to detect the thrombocytopenia and identify the high risk of poor prognosis.